Instytucje demokracji bezpooeredniej w procesie integracji europejskiej – od referendum ogólnonarodowego do europejskiej inicjatywy obywatelskiej - MUSIAŁ-KARG, MAGDALENA (Rocznik Integracji Europejskiej, 2012)
The idea of civic participation in national decision-making processes is an important part of European history. By means of implementing the principle of the sovereignty of nations, those eligible to vote are able to express their will through the institutions of direct democracy and representative democracy. The instruments of direct democracy are an extremely interesting research subject – not only due to the fact that the number of votes on European integration has been very high (especially in the last decade), but also because EU Member States, being aware of the importance of citizen involvement in the process of integration in Europe, established the institution of the European citizens’ initiative. Using this instrument, European citizens can impact the politics of the EU. The purpose of this text is to answer the question of the role of direct democracy and its tools in the process of European integration, as well as of the prospects for the use of direct forms of governance in the process of deepening and widening integration in Europe.